Ações afirmativas e o debate sobre racismo no Brasil - Hofbauer, Andreas [UNESP] (FapUNIFESP (SciELO), 2006)
The affirmative action issue has split the public opinion and heated up the academic debate. While some experts and black activists see the affirmatives actions as a way to fight racism, since the positive discrimination could help the historically underprivileged to create and empower a positive identity, others see such measures as a dangerous attack against the traditional brazilian way of dealing with human differences. The latter fear that such policies may unleash racial conflicts. Although both sides barely explain what they mean for racism and how they understand that social phenomenon, it is possible to discern in those discourses different lines of argument, which can be related to different theoretical orientations about the analysis of such concepts as race and color.
Afirmative actions and the debate on racism in Brazil
Keywords: Afirmative actions; Brazil; Racism; Social theory